The role of communication concerning employees in successful privatization: the case of Sanpaolo Bank's acquisition of Egypt's Bank of Alexandria - El Agamy, Mahmoud (AUC Knowledge Fountain, 2011)
This research explores the role of communication in the privatization process. It presents a case study of Intesa Sanpaolo Bank's acquisition of the Egyptian Bank of Alexandria. The challenges faced included labor retrenchment and job losses, benefit losses, and nationalization fears. The main sources for gathering the information were interviews with the managers and a survey instrument. The analysis examines employee opinions and fears and whether opinions changed as a result of the communication process during the privatization, based on data collected from senior bank officials and a survey of employees in a representative bank branch. A survey of 23 management-level employees was conducted to collect information on employee concerns and attitudes and their communication experience throughout the privatization process. The analysis found that the employees are generally satisfied with the communication process, but that managers did not convince them of privatization's value for the nation, for the bank, or for themselves. The survey showed that effective communication during privatization implementation contributed to the smooth operation of the privatized enterprise in the employees' view: those employees having positive feelings toward the culture of the incoming bank and the privatization process overall were more likely to find that the communications process addressed their fears. Good communications on the rationale for the privatization and its benefits can play an important role in improving post-privatization performance, helping employees to adapt to the new culture and to cross national cultural borders successfully. Employee concerns about their personal status after privatization were generally resolved, but employees had greater concerns about the impact on the bank. Many employees felt that the new bankÃƒÂ¢ s culture was very different from their own. Most disagreed that privatization would benefit the bank or the country in the long term. These findings show that employees may be uncertain regarding the effects of the privatization on their institution and on themselves. New managers must respond to both concerns to shape employee's perceptions of fairness and optimism within the organization. Understanding and responding to employee perceptions and opinions on the changes underway are both essential for improving employee performance in the post-privatization workplace.